Relationship Between Fibroblast Growth Factor 19 and Diabetic Retinopathy in Patients with Type 2 Diabetes Mellitus - Chung JO (Dove Medical Press, 2021)
Jin Ook Chung,1 Seon-Young Park,2 Dong Hyeok Cho,1 Dong Jin Chung,1 Min Young Chung1 1Division of Endocrinology and Metabolism, Department of Internal Medicine, Chonnam National University Medical School, Gwangju, 501-757, Republic of Korea; 2Division of Gastroenterology and Hepatology, Department of Internal Medicine, Chonnam National University Medical School, Gwangju, 501-757, Republic of KoreaCorrespondence: Jin Ook Chung; Min Young ChungDivision of Endocrinology and Metabolism, Department of Internal Medicine, Chonnam National University Medical School, 8 Hak-Dong, Dong-Gu, Gwangju, 501-757, Republic of KoreaTel +82-62-220-6296; +82-62-220-6297Fax +82-62-225-8578Email imagine-jjo@hanmail.net; jrjjo222@gmail.comAim: This study aimed to evaluate whether fibroblast growth factor 19 (FGF19) is associated with the risk of diabetic retinopathy in patients with type 2 diabetes mellitus (T2DM).Methods: A total of 357 patients with T2DM were investigated in this cross-sectional study. Logistic regression analysis was performed to assess the association between FGF19 level and diabetic retinopathy.Results: Serum FGF19 level was significantly lower in patients with diabetic retinopathy in those without diabetic retinopathy. The multivariable analysis revealed a significant association between serum FGF19 level and diabetic retinopathy (odds ratio for every 1 standard deviation increase in logarithmic value = 0.69, 95% confidence interval 0.51– 0.94, p = 0.019).Conclusion: Serum FGF19 level was negatively associated with diabetic retinopathy in patients with T2DM.Keywords: diabetic retinopathy, fibroblast growth factor 19, type 2 diabetes mellitus